PENGARUH PELATIHAN KERJA DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SOLUSI MITRA TAMA JAKARTA UTARA - Maryadi Maryadi; Mohamad Duddy Dinantara (Al Hasanah Barokah Foundation, 2025)
This study aims to analyze the influence of job training and organizational communication on employee performance at PT. Solusi Mitra Tama North Jakarta. This study uses a quantitative approach with an associative method. The number of respondents was 52 people obtained through saturated sampling techniques. Data analysis techniques are in the form of validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests. The results showed that job training had a positive and significant effect on employee performance, with a regression equation Y = 10.810 + 0.726X1, a significance value of 0.000 < 0.05 and a regression coefficient value of 0.726, a correlation coefficient value of R = 0.771 meaning that the two variables had a strong relationship. The hypothesis test was obtained from t calculation > t table or (8.567 > 2.0086), the value of sig. (0.000 < 0.05) means that Ho1 is rejected and Ha1 is accepted. Organizational communication also has a positive and significant effect on employee performance, with a regression equation Y = 10.832 + 0.751X2 with a significance value of 0.000 and a regression coefficient of 0.751, the value of the correlation coefficient R = 0.786 means that the two variables have a strong relationship. The hypothesis test was obtained in the t calculated > table or (8.987 > 2.0086), the value sig. (0.000 < 0.05) means that Ho2 is rejected and Ha2 is accepted. Simultaneous job training and organizational communication have a positive and significant effect on employee performance, with regression results Y = 9.834 + 0.283X₁ + 0.484X₂, the value of F calculated > F table or (41.713 > 3.19) and a significance of 0.000 means that Ho3 is rejected and Ha3 is accepted. An R-square value of 0.630 indicates that the two independent variables explain 63% of employee performance variability.